The association between epilepsy and COVID-19: analysis based on Mendelian randomization and FUMA - You, Mingyao; Yuan, Ping; Li, Liangqian; Li, Baoduo; Peng, Zijun; Xu, Hongbei (Frontiers in Neuroscience, 2023)
Objective: A multitude of observational studies have underscored a substantial comorbidity between COVID-19 and epilepsy. This study was aimed at establishing a conclusive causal link between these two conditions.We employed Mendelian randomization (MR) to evaluate the causal link between COVID-19 and epilepsy, as well as its focal and generalized subtypes. The GWAS for epilepsy and its subtypes database were abstracted from both FinnGen consortium and ILAE. Additionally, we leveraged functional mapping and annotation (FUMA) to integrate information from genome-wide association studies (GWAS) results.The MR analyses revealed that genetic liability to COVID-19 infection conferred a causal effect on epilepsy